Social and Cultural Implications of Da'wah Through Social Media - Bahrudin, Memet Isa; Waehama, Muhammad Roflee (Jurnal Iman dan Spiritualitas, 2024)
This study aims to explore the use of social media in Islamic preaching in the digital age and the challenges faced in spreading religious messages through digital platforms. Using a descriptive qualitative approach, this research relies on a literature review to collect secondary data related to the use of media in preaching. The findings indicate that social media platforms such as YouTube, Instagram, and TikTok have opened significant opportunities for preaching to reach a global audience effectively and creatively. However, the study also identifies challenges related to message distortion, lack of content credibility, and the dissemination of inaccurate information. This research proposes strategic guidelines to maximize the potential of social media in spreading Islamic values while mitigating possible risks. In conclusion, social media holds great potential for preaching, but it requires a cautious and responsible approach to ensure that religious messages remain accurate and beneficial. It is recommended that preachers utilize social media creatively while maintaining the essence and integrity of religious teachings.